Mengelola Toyomarto Menuju Desa Wisata Terintegrasi Berbasis Digital - Rina Rahmawati; Evi Maria; Dwi Nita Aryani; Widanarni Pudjiastuti; Sugeng Hariadi; Bunyamin; Siti Munfaqiroh (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Toyomarto Village in Singosari District, Malang has the potential to be developed as an integrated digital-based tourism destination. This community service activity aims to create synergies between tourism villages, communities, and other related institutions and stakeholders; improve the competence of human resources managing tourism villages; develop integrated education trip tour packages; and increase economic benefits for the wider community. Implementation of methods included FGDs and training of Pokdarwis and managers. The results achieved that the increasing of the capacity of tourism village managers in financial management and digital marketing; developing of integrated education trip tour packages; and increasing the cooperation between tourism stakeholders in Toyomarto Village. In conclusion, assistance in managing Toyomarto Tourism Village in an integrated manner can make this village a sustainable digital-based tourism village towards a global tourism village.